2012
DOI: 10.3390/catal2030330
|View full text |Cite
|
Sign up to set email alerts
|

Superior MgH2 Kinetics with MgO Addition: A Tribological Effect

Abstract: Abstract:The kinetics of hydrogen absorption/desorption in magnesium can be improved without any catalysis assistance and MgO was found to be more effective than the best catalyst reported so far, i.e., Nb 2 O 5 . Herein, a quantitative analysis of the hydrogen kinetics in magnesium modified with MgO was performed in order to identify possible rate controlling mechanisms. While hydrogen absorption was found to be diffusion controlled as commonly reported, hydrogen desorption evolved from nucleation and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Furthermore, previous studies have shown that the sorption performance in MgH 2 can be enhanced with the addition of MgO. Ares-Fernández and Aguey-Zinsou 45 claimed that the addition of MgO to MgH 2 during the milling process led to an enhancement of sorption kinetics because of the high electronegativity MgO. In another study, the same group also claimed that during the milling process, MgO may act as a process control agent that can lead to the reduction of the particle agglomeration of MgH 2 by an optimal breakage rate, thus aiding the high stability of these particles and evading the use of cold welding.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies have shown that the sorption performance in MgH 2 can be enhanced with the addition of MgO. Ares-Fernández and Aguey-Zinsou 45 claimed that the addition of MgO to MgH 2 during the milling process led to an enhancement of sorption kinetics because of the high electronegativity MgO. In another study, the same group also claimed that during the milling process, MgO may act as a process control agent that can lead to the reduction of the particle agglomeration of MgH 2 by an optimal breakage rate, thus aiding the high stability of these particles and evading the use of cold welding.…”
Section: Resultsmentioning
confidence: 99%
“…Severe plastic deformation (SPD) technique [15], including high energy ball milling [16], cold rolling (CRing) [17,18], high pressure torsion (HPT) [19] and equal channel angular pressing (ECAP) [20] were employed to improve the hydrogen storage properties of MgH 2 . Apart from the mechanical treatment approach, catalyzation MgH 2 powders with proper volume fractions of catalytic agents [21], including pure metals [22], intermetallic compounds [23][24][25][26], metal-oxides [27,28], metal/metal oxide composites [5,29], -carbides [30,31], metallic glassy alloys [32][33][34] and chlorides [35] have shown outstanding effects on enhancing the hydrogen storage properties of MgH 2 and infer its apparent activation energy of decomposition [36]. More recently, self-assembled MgH 2 and metal borohydride nanoparticles on graphene technique has shown great enhancement of the behavior of the metal hydride phase [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one such additive to nitrile-butadiene rubber (NBR) is magnesium oxide (MgO) and magnesium is known to hydride in the presence of hydrogen gas. [33][34][35] Damaging effects to the base polymer may include bubble or void formation, surface blistering, dilation, changes in modulus and strength, changes in friction and wear, and other changes associated with the absorption of a relatively high amount of hydrogen. 36 Additionally, since the saturation hydrogen concentration in polymers is proportional to the exterior pressure, it is thus expected that the damaging effects are more significant at higher pressures.…”
Section: Introductionmentioning
confidence: 99%